2021
DOI: 10.1016/j.xphs.2020.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Weight and Composition With Hepatic Activities of Cytochrome P450 Enzymes

Abstract: Obesity is associated with comorbidities of which pharmacological treatment is needed. Physiological changes associated with obesity may influence the pharmacokinetics of drugs, but the effect of body weight on drug metabolism capacity remains uncertain. The aim of this study was to investigate ex vivo activities of hepatic drug metabolizing CYP enzymes in patients covering a wide range of body weight. Liver biopsies from 36 individuals with a body mass index (BMI) ranging from 18 to 63 kg/m 2 were obtained. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 41 publications
(27 reference statements)
4
46
0
Order By: Relevance
“…11,44 Further, the present study supports previous findings of an inverse relationship between BMI and oral clearance of CYP3A substrates (Figure 3c). 10,12,13 Given that we assessed both absolute bioavailability and clearance, we can argue that the negative association between BMI and oral clearance is explained by both higher bioavailability and clearance with higher body weight, but that the effect on bioavailability was greater. The protein quantification in the present study supports previous findings of a lower hepatic CYP3A expression and activity in patients with severe obesity 12,13 and in patients with NAFLD (Figure 3f,h).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,44 Further, the present study supports previous findings of an inverse relationship between BMI and oral clearance of CYP3A substrates (Figure 3c). 10,12,13 Given that we assessed both absolute bioavailability and clearance, we can argue that the negative association between BMI and oral clearance is explained by both higher bioavailability and clearance with higher body weight, but that the effect on bioavailability was greater. The protein quantification in the present study supports previous findings of a lower hepatic CYP3A expression and activity in patients with severe obesity 12,13 and in patients with NAFLD (Figure 3f,h).…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing RYGB, small intestinal and hepatic biopsies were obtained on the day of surgery, as previously described. 13,25 Hepatic biopsies were also obtained from the control group during cholecystectomy. 13 Patients abstained from food and drugs from 10:00 p.m. the evening before all pharmacokinetic investigations.…”
Section: Studyvisitsandproceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Dashed lines represent the lines of unity for reference, and blue lines represent a linear regression passing through the origin for better visualization of misspecification. The slope of this regression line is 1.26, 1.22, 1.20, and 1.18 for (a-d), respectively enzymes in adults, such evidence is lacking in children with obesity [36,37]. Few clinical studies are reported in children with obesity determining changes in metabolism using in vivo data, and those that exist conflict with known changes in adults with obesity [38], possibly owing to lower rates of comorbidities in children.…”
Section: Drug-metabolizing Enzymes and Transportersmentioning
confidence: 96%
“…Therefore, information regarding CYP levels in subpopulations is needed. There are numerous examples of subpopulations with altered CYP levels, to mention a few: Obese have reduced CYP3A activity with increasing bodyweight 4 ; Pregnant have increased activity of CYP2D6 and CYP3A4 and reduced CYP1A2 activity 5 ; Individuals suffering from cirrhosis have markedly reduced activity of CYP1A2 and CYP3A4. 6 …”
Section: Introductionmentioning
confidence: 99%